As permutações caóticas, o problema de Lucas e a teoria dos permanentes - Nunes, Alexmay Soares (2015)
In this work we cover some counting techniques used to solve some classic problems in Combinatorics. We also show a link between the so called “rencontre problem”, the “ménage problem” and the permanent of a square matrix.